Respuesta :
Step-by-step explanation:
Let the first term of the arithmetic sequence be a and common difference be d
Then, t2 = -5
or, a+(n-1)d= -5
or, a+(2-1)d= -5
or,a+ d = -5 ---------------(i)
Again, t6= 7
or, a+(6-1)d= 7
or, a + 5d = 7------------(ii)
Now equation (ii) - (i),
a+5d - ( a+d)= 7-(-5)
a+5d-a-d = 7+5
4d= 12
d = 3
From equation (i),
a +d=-5
a+3= -5
a=-5-3 = -8
t5 = a+(5-1)d
= -8+4(3)
= -8+12
= 4
Answer:
The fifth term is 4.
Step-by-step explanation:
The model for an arithmetic sequence is a(n) = a(1) + d(n -1), where d is the common difference. Using the given information, we get:
a(2) = a(1) + d(2 - 1) = -5, or a(1) + d = -5
a(6) = a(1) + d(6 - 1) = 7, or a(1) + 5d) = 7
Here we have two equations in two unknowns: a(1) and d.
Subtract the first equation from the second:
a(1) + 5d = 7
-a(1) - d = 5
--------------------
4d = 12
Thus, d = 12/4 = 3. This is the common difference.
Use the equation a(1) + d = -5 (from above) to find the value of a(1):
a(1) + 3 = -5, or a(1) = -8
Then the equation for this arithmetic sequence is a(n) = -8 + 3(n - 1).
The 5th term of this sequence is thus
a(5) = -8 + 3(5 - 1), or a(5) = -8 + 3(4), or -8 + 12, or 4.